On the Gas Heating Mechanism for the Fast Anode Arc Reattachment in a Non-transferred Arc Plasma Torch Operating with Nitrogen Gas in the Restrike Mode. - Prevosto, Leandro; Kelly, Héctor; Mancinelli, Beatriz; Chamorro, Juan Camilo (My University, 2015)
The present work provides a detailed kinetic analysis of the time-resolved dynamics of the gas heating during the arc reattachment in nitrogen gas in order to understand the main processes leading to such a fast reattachment. The model includes gas heating due to the relaxation of the energy stored in the vibrational as well as the electronic modes of the molecules. The results show that the anode arc reattachment is essentiality a threshold process, corresponding to a reduced electric field value of E/N * 40 Td for the plasma discharge conditions considered in this work. The arc reattachment is triggered by a vibrational instability whose development requires a time of the order of 100 ls. For E/N\80–100 Td, most of the electron energy is transferred to gas heating through the mechanism of vibrational–translational relaxation. For larger values of E/N the electronic– translational energy relaxation mechanism produces a further intensification of the gas heating. The sharp increase of the gas heating rate during the last few ls of the vibrational instability give rises to a sudden transition from a diffuse (glow-like) discharge to a constricted arc with a high current density (*107 A/m2 ). This sudden increase in the current density gives rise to a new anode attachment closer to the cathode (where the voltage drop between the original arc and the anode is the largest) thus causing the decay of the old arc spot.
Keywords: Anode arc reattachment.; Vibrational instability.; Fast gas heating.; Plasma torches.